MANAJEMEN HUMAS DI PONDOK PESANTREN AL BADR BANGKINANG - Fatmawati Mahabu; Nadya Tri Puji Lestari; Rini Sekarsari (STKIP Pesisir Selatan, 2026)
This study aims to describe and analyze public relations management at Pondok Pesantren Al Badr Bangkinang in strengthening institutional branding and image, supporting student recruitment, and developing pesantren programs. This research employs a descriptive qualitative approach with data collected through in-depth interviews, participant observation, and documentation. The results show that the public relations team at Pondok Pesantren Al Badr Bangkinang plays an active role in building a positive institutional image through the use of social media, socio-religious activities, and personal communication with the community. These strategies not only increase public trust but also effectively contribute to the growing number of student applicants each year. Supporting factors in public relations implementation include leadership support, collaborative team spirit, and alumni involvement. Meanwhile, the inhibiting factors include limited professional human resources, the absence of a formal standard operating procedure (SOP) for public relations, and budget constraints. This study recommends that the pesantren strengthen its public relations organizational structure, enhance human resource capacity through training, and utilize digital media optimally to meet the challenges of public communication in the modern era.